Pengembangan Instrumen Penılaıan Karakter Rasa Ingın Tahu Dalam Pembelajaran Membaca Dan Menulıs Sıswa Kelas 1 SD - Hilary Sekarningrum; Yuliana Setyaningsih; B. Widharyanto (Elementary Teacher Education Program, Majalengka University, 2023)
Currently, the assessment of curiosity character education is mostly done by observation. The lack of innovation in developing curiosity character assessment instruments for elementary school students is the background of this research. The purpose of this study was to develop an instrument for assessing the character of curiosity in teaching reading and writing to elementary school students. This study uses the ADDIE Research and Development method. This study involved 15 teachers for needs analysis, three lecturers and four teachers for surface and content validation, and 17 grade 1 elementary school students for testing the curiosity character assessment instrument. The research instruments used in this study were tests and non-tests, using closed and open questionnaires. Data analysis techniques in this study were carried out quantitatively and qualitatively. The results showed that the curiosity character assessment instrument was developed by following the steps of the ADDIE development procedure which had been tested for quality with